Effects of Vaccination on Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Nationwide Population-Based Cohort Study - Sang Hyuk Kim; Hyun Lee; Min Ji Kim; Min Gu Kang; Jong Seung Kim; Jong Geol Jang; Youlim Kim; Hyeon-Kyoung Koo; Chin Kook Rhee; Kyung Hoon Min; Yong Il Hwang; Deog Kyeom Kim; et al. (Tuberculosis and Respiratory Diseases, 2025)
Background Coronavirus disease 2019 (COVID-19) vaccination may offer benefits for patients with chronic obstructive pulmonary disease (COPD). However, the evidence on whether the vaccination decreases the frequency of acute exacerbation of COPD (AECOPD) is limited. Methods This study enrolled 41,606 individuals diagnosed with COPD using the Korean National Health Insurance System-severe acute respiratory syndrome coronavirus 2 (NHIS SARS-CoV-2) database between 2020 and 2021. A cohort of 3,602 individuals was analyzed through 1:1 propensity score matching of vaccinated and unvaccinated groups. The risk of AECOPD was evaluated using a Cox proportional hazards regression analysis. A post hoc analysis examined the impact of COVID-19 on AECOPD in vaccinated and unvaccinated groups among infected and uninfected subgroups. Results Throughout the study, the exacerbation rate was lower in the vaccinated group (1,683/10,000 person-years) compared to the unvaccinated group (3,410/10,000 personyears). The Cox proportional hazards model showed a significantly decreased risk of AECOPD in vaccinated individuals relative to unvaccinated individuals (hazard ratio [HR], 0.55; 95% confidence interval [CI], 0.41 to 0.72). post hoc analysis revealed that COVID-19 was associated with a higher risk of AECOPD in unvaccinated individuals (adjusted HR, 2.06; 95% CI, 1.28 to 3.33), while in vaccinated individuals, the risk did not significantly differ between those infected and not infected with COVID-19 (adjusted HR, 1.35; 95% CI, 0.42 to 4.36). Conclusion COVID-19 vaccination appears to decrease the risk of AECOPD among individuals with COPD.